Brachodes norbertkeili sp. nov., a remarkable new species from Kyrgyzstan (Lepidoptera, Brachodidae, Cossoidea) - Huemer, Peter; Kallies, Axel (Zootaxa, 2025)
Brachodes norbertkeili sp. nov. is described based on specimens collected in Kyrgyzstan. This new species is related to Brachodes fallax (Staudinger, 1900), Brachodes staudingeri Kallies 1998 and allied taxa but it differs significantly in terms of its external appearance, particularly with regards to its extraordinary size and the extended cream suffusion of the forewing. Furthermore, the new species is separated from its congeners by its CO1 sequence. The adult and male genitalia of the new species are illustrated. The type locality is in a remote area, which is home to local endemism even in butterflies and several likely undescribed species from various families, suggesting long-lasting isolation.